Tumor Immune-Infiltrate Landscape After Chemo-Radiotherapy in a Case Series of Patients with Non-small Cell Lung Cancer: Pretreatment Predictors and Correlation With Outcome. (31st January 2022) - Pavan, Alberto; Ferro, Alessandra; Fortarezza, Francesco; Schiavon, Marco; Evangelista, Laura; Pezzuto, Federica; Lunardi, Francesca; Frega, Stefano; Bonanno, Laura; Rea, Federico; Guarneri, Valentina; Conte, PierFranco; et al.
Abstract: Introduction: Data on tumor immune-milieu after chemo-radiation (CT-RT) are scarce. Noninvasive tools are needed to improve the treatment of non–small cell lung cancer (NSCLC), especially in the locally advanced (LA) setting. Methods: We collected a series of superior-sulcus (SS)- patients with NSCLC referred to our Institute (2015-2019), eligible for a preoperative CT-RT. We characterized tumor-infiltrating immune cells (TIICs), determined PD-L1-TPS and the residual viable tumor cells (RVTC). Radiological and metabolic responses were reviewed. We calculated pre-surgery neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). Results: Eight patients were included. Radiological responses were 6 disease stabilities (SD) and 2 partial responses (PR). Metabolic responses were 4 SD and 4 PR. CD68+-TIICs were correlated with metabolic response and lower RVTC. CD68+-TIICs were associated with higher PLR. Higher PLR values seemed linked with lower RVTC. Conclusions: These preliminary results could be useful for consolidation treatment selection for patients with LA-NSCLC without evaluable baseline PD-L1 and higher PLR values. Abstract : Data on tumor immune-milieu after chemo-radiotherapy (CT-RT) are scarce. The aim of this study was to describe histological features of tumor specimens after CT-RT, to correlate them with response, and to find new tools for the prediction of tumor immune-milieu, which may overlook tissue re-biopsy in locally advanced non-small cell lung cancer.